2014
DOI: 10.1074/jbc.m114.571141
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Clock Regulates Daily α1–2-Fucosylation of the Neural Cell Adhesion Molecule (NCAM) within Mouse Secondary Olfactory Neurons

Abstract: Background: Mammalian olfaction has circadian rhythm, and glycosylation plays critical roles in the olfactory system. Results: ␣1-2-Fucosylation increases during the nighttime in axons of secondary olfactory neurons in WT but not in Clock mutant mice. Conclusion: Rhythmic ␣1-2-fucosylation governed by clock genes is a potential mechanism of circadian olfaction. Significance: Glycosylation in the central nervous system is circadian.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…7 a). Alpha1-2Fuc glycan mediates neuronal functions, affects neuronal morphology [Pohle et al, 1987;Krug et al, 1991Krug et al, , 1994Matthies et al, 1996;Lorenzini et al, 1997;Kalovidouris et al, 2005;Murrey et al, 2006] and also might control olfactory functions according to developmental stage [Murrey et al, 2009] and circadian rhythms [Kondoh et al, 2014]. We showed that most receptor cells arranged at the basal region of the OE possess dendrites and axons including α1-2Fuc glycan; this agrees with the findings reported by Ducray et al [1999].…”
Section: Uea-i Reaction In the Aobsupporting
confidence: 83%
See 4 more Smart Citations
“…7 a). Alpha1-2Fuc glycan mediates neuronal functions, affects neuronal morphology [Pohle et al, 1987;Krug et al, 1991Krug et al, , 1994Matthies et al, 1996;Lorenzini et al, 1997;Kalovidouris et al, 2005;Murrey et al, 2006] and also might control olfactory functions according to developmental stage [Murrey et al, 2009] and circadian rhythms [Kondoh et al, 2014]. We showed that most receptor cells arranged at the basal region of the OE possess dendrites and axons including α1-2Fuc glycan; this agrees with the findings reported by Ducray et al [1999].…”
Section: Uea-i Reaction In the Aobsupporting
confidence: 83%
“…For example, we showed that α1-2Fuc glycan preferentially locates in the LOT and in the glomerular layer of the AOB of the ICR mouse [Kondoh et al, 2014] whereas other study groups have not found that UEA-I reacts with the mouse LOT. Because of the potential of α1-2Fuc glycan described above, identifying the histological components and cell types that α1-2Fuc glycan modifies in the olfactory system is important.…”
mentioning
confidence: 78%
See 3 more Smart Citations